A stacked solid electrolytic capacitor and a manufacturing method thereof
By adopting a stacked multi-layer structure, the solid-state electrolytic capacitor uses a highly conductive metal electrode layer, a composite electrolyte layer and an isolation layer, combined with high-voltage heat treatment technology, the problem of insufficient performance of solid-state electrolytic capacitors under high frequency and high temperature conditions is solved, and efficient, reliable and low-cost capacitor manufacturing is achieved.
Patent Information
- Application Number
- CN202411899012.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-04
AI Technical Summary
The existing solid-state electrolytic capacitors have insufficient performance under high frequency and high temperature conditions, and the ion migration resistance in solid-state materials is large, resulting in low capacitor efficiency, poor quality of material bonding and high cost, which limits its large-scale application.
A solid-state electrolytic capacitor adopts a stacked multi-layer structure. Each layer consists of a highly conductive metal electrode layer, a composite electrolyte layer and an isolation layer. It is closely combined through high-pressure heat treatment to improve capacitance and mechanical strength.
It improves the performance of capacitors under high frequency and high temperature conditions, enhances the overall efficiency and reliability of capacitors, reduces manufacturing costs, and promotes large-scale applications.
Smart Images

Figure CN119764060A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of capacitor technology, and more specifically to a stacked solid electrolytic capacitor and its manufacturing method. Background Technology
[0002] Solid-state electrolytic capacitors are a new type of electronic component that solves common problems in traditional capacitors, such as leakage, electrolyte evaporation, and poor temperature stability, by using solid electrolytes instead of traditional liquid or semi-solid electrolytes.
[0003] In related technologies, the low ion transport efficiency of solid electrolytes limits the performance of capacitors under high frequency and high temperature conditions. At the same time, the high resistance to ion migration in solid materials affects the overall efficiency of the capacitor. Since the contact between solids is usually poor, high impedance is easily generated at the electrode and electrolyte interface, which reduces the energy storage efficiency of the capacitor and may even lead to performance degradation. Current solid electrolytic capacitors usually adopt a laminated structure, but in multilayer manufacturing, it is difficult to guarantee the bonding quality between materials, resulting in a decrease in reliability. In addition, the manufacturing process requires special material handling technology, which is costly and limits its large-scale application. To address these issues, we propose a stacked solid electrolytic capacitor and its manufacturing method.
[0004] The information disclosed in this background section is only for understanding the background technology of the inventive concept, and therefore may include information that does not constitute prior art. Summary of the Invention
[0005] To overcome the shortcomings of existing technologies, this invention provides a stacked solid-state electrolytic capacitor and its manufacturing method to address the issues raised in the background art, such as the low ion transport efficiency of solid electrolytes, which limits the performance of capacitors under high-frequency and high-temperature conditions; the high resistance to ion migration in solid materials, which affects the overall efficiency of the capacitor; the typically poor contact between solids, which easily leads to high impedance at the electrode-electrolyte interface, reducing the energy storage efficiency of the capacitor and potentially causing performance degradation; and the fact that current solid-state electrolytic capacitors typically employ a laminated structure, but in multilayer manufacturing, the bonding quality between materials is difficult to guarantee, resulting in decreased reliability. Furthermore, the manufacturing process requires special material handling techniques, leading to high costs and limiting its large-scale application.
[0006] The technical solution adopted by the present invention to solve its technical problem is: a stacked solid electrolytic capacitor, including a capacitor body, wherein the capacitor body adopts a multi-layer stacked structure, and each layer consists of an electrode layer, a solid electrolyte layer and an isolation layer;
[0007] The electrode layer includes a positive electrode layer and a negative electrode layer, and is made of a highly conductive metal responsible for conducting charges. It can be made of either aluminum or tantalum.
[0008] The fixed electrolyte layer uses a composite electrolyte to provide ion transport channels. The composite electrolyte can be either a polyethylene oxide (PEO)-based composite solid electrolyte or a polyvinylidene fluoride (PVDF)-based composite solid electrolyte.
[0009] The isolation layer prevents direct contact between the motor and the ion path;
[0010] The multi-layer stacked structure increases the effective electrode contact area per unit area and improves the capacitance.
[0011] Each layer of components in the stack is tightly bonded through high-pressure heat treatment to improve interface compatibility and mechanical strength.
[0012] A method for manufacturing a stacked solid electrolytic capacitor, the manufacturing steps of which are as follows:
[0013] A: Multi-step lamination:
[0014] (a1: Prepare materials for each layer: First, prepare the raw materials for the electrode layer, electrolyte layer and isolation layer, and ensure that the size, thickness and chemical properties of each material meet the requirements;
[0015] (a2: Pretreatment and cleaning: Before stacking, each layer of material is cleaned to remove surface impurities and oxides, ensuring good interlayer bonding;
[0016] (a3: Lamination stacking: Using a special laminator, the layers of material are stacked in sequence and appropriate pressure is applied. During multiple stacking processes, it is necessary to ensure that each layer of material is free from misalignment, air bubbles or defects.)
[0017] (a4: Heat treatment and cooling: The stacked components are heated to a certain temperature, which is set between 120°C and 200°C. Through heat treatment, the molecules between the materials are cross-linked to a certain extent, which enhances the interlayer bonding force.)
[0018] B: Vacuum sintering:
[0019] (b1: Stack heating: Sintering is carried out in a vacuum furnace at a temperature controlled between 300°C and 500°C. This temperature is sufficient to promote molecular movement in the material, but will not cause excessive thermal damage to the material.)
[0020] (b2: Create a vacuum environment: Remove residual gas and moisture from the material by vacuuming, further reduce the generation of bubbles and enhance the compactness of the material;
[0021] (b3: Cooling: After sintering, slowly cool to room temperature to avoid thermal stress caused by sudden temperature drop;
[0022] C: Laser cutting:
[0023] (c1: Size measurement: Measure the overall dimensions of the stack using precision instruments according to the design dimensions and requirements of the capacitors;)
[0024] (c2: Laser cutting: High-precision laser cutting equipment is used to cut the stack to ensure the flatness of the cut surface and the accuracy of the cut dimensions;
[0025] (c3: Post-processing: After cutting, edge treatment or cleaning is required to remove small particles or heat-affected zones generated during the cutting process.)
[0026] As an optimized technical solution, the fabrication of composite solid electrolytes is also included, with the following steps:
[0027] Preparation of inorganic materials:
[0028] Highly conductive sulfide and oxide materials are used as matrix materials. Sulfides are characterized by their high ionic conductivity (up to 10 mS / cm) and mechanical flexibility, while oxides help stabilize interfacial chemistry and reduce interfacial resistance. Specifically, the sulfide materials used are the Li₂S-P₂S₅ system or Li₆PS₅X, where X = Br, Cl, I; and the oxide materials used are LiNbO₃ and Li₄Ti₅O₃. 12 One of them;
[0029] Polymer solution preparation:
[0030] Polyvinylidene fluoride (PVDF) is mixed with N-methylpyrrolidone solvent to form a homogeneous solution. These polymers play a role in bonding and flexibility modification in composite materials.
[0031] Mixing of composite materials:
[0032] Inorganic material powder and polymer solution are mixed in a ratio of 1:1.2. The mixture is then dispersed by ultrasonication or ball milling to ensure uniform material distribution. This step can improve the ion transport path and increase the overall ionic conductivity.
[0033] Membrane forming and heat treatment:
[0034] The mixture is coated or pressed into a film and then heat-treated at high temperatures, controlled between 150°C and 200°C, to enhance the interfacial bonding between the sulfide and the polymer, thereby improving mechanical strength and ionic conductivity.
[0035] As an optimized technical solution, adding dopants to composite solid electrolytes can optimize ion transport pathways and improve chemical stability. The steps are as follows:
[0036] Selecting the dopant: Choose either a lithium salt or a conductive ceramic based on the target performance. The lithium salt can be either LiCl or LiTFSI, and the conductive ceramic can be Li7La3Zr2O. 12 ;
[0037] Uniform dispersion: Lithium salt and ceramic particles are mixed in a specific ratio and uniformly dispersed in a polymer matrix (polyvinylidene fluoride). The ratio of lithium salt to ceramic particles is controlled between 1:1.5 and 1:2.
[0038] Heat treatment and curing: High-temperature heat treatment promotes interfacial fusion of materials, thereby reducing interfacial resistance.
[0039] As an optimized technical solution, an interface conditioning layer is also applied to the contact surface between the motor and the electrolyte. The purpose is to reduce the interface impedance and improve the bonding quality between the electrode and the electrolyte. The steps are as follows:
[0040] S1: Coating of the interface conditioning layer:
[0041] Conductive polymer coating: Polyaniline (PANI) and polypyrrole (PPy) conductive polymers are used to form a conductive bridge between the electrode and the electrolyte, reduce interfacial impedance, and enhance the migration of electrons and ions on the electrode surface;
[0042] Oxide coating: A thin layer of titanium oxide (TiO2) or aluminum oxide (Al2O3) is formed on the electrode surface. This oxide layer can prevent direct contact between the electrode and the electrolyte, reduce chemical reactions, and provide a stable interface.
[0043] S2: Plasma treatment:
[0044] By using plasma to create minute structural changes on the electrode surface, including porosimetry or surface activation, the binding force between the electrode surface and the electrolyte can be improved. Plasma treatment can clean the electrode surface and effectively activate the surface, thereby improving the reactivity at the interface.
[0045] The process involves plasma treatment of the electrode surface with a gas, which can be oxygen, nitrogen or argon, to form abundant oxygen functional groups, including -COOH and -OH, thereby enhancing the physical and chemical bonding between the electrode and the electrolyte.
[0046] S3: Chemical modification:
[0047] Different functional groups can be introduced onto the electrode surface to improve the interfacial stability between the electrode and the electrolyte. These groups can form coordination or chemical bonds with ions in the electrolyte, enhance interfacial adhesion, and thus reduce resistance. Functional groups include amino and carboxyl groups.
[0048] As an optimized technical solution, to improve the environmental resistance of capacitors, including moisture resistance, high temperature resistance, and corrosion resistance, and to optimize the internal structural design to reduce the decay of electrolyte conductivity at low temperatures, a protective coating is added.
[0049] The steps are as follows:
[0050] Coating selection: Select coating materials suitable for high temperature and humid environments, including fluoride coatings or ceramic coatings, which have excellent corrosion resistance, high temperature resistance and moisture resistance. Fluoride coatings can be made of fluorinated polytetrafluoroethylene, and ceramic coatings can be made of alumina or titanium dioxide.
[0051] Surface treatment: The capacitor surface is treated, including plasma cleaning and chemical pretreatment, to improve the adhesion and uniformity of the coating;
[0052] Coating application: Applying a coating by spraying, dipping, brushing, or chemical vapor deposition;
[0053] Curing: Heat treatment is used to cure the coating, improving its durability and adhesion.
[0054] As an optimized technical solution, it also includes introducing conductive networks or nanostructured pathways into the electrolyte to optimize ion diffusion. The steps are as follows: 1: Select conductive network or nanostructured materials:
[0055] Conductive polymers: Polyaniline (PANI), polypyrrole (PPy), or polyethylene terephthalate (PET) conductive polymers are selected, which have good conductivity and high flexibility, and are suitable for optimizing the ion conduction of electrolytes;
[0056] Conductive ceramics: Alumina (Al2O3), zinc oxide (ZnO) or Li6PS5X are selected to effectively improve the ionic conductivity of the electrolyte, especially in high and low temperature environments;
[0057] Carbon nanomaterials: Carbon nanotubes (CNTs) or graphene are selected because their excellent conductivity and high surface area can significantly improve the conductivity of electrolytes and optimize ion migration pathways.
[0058] 2: Preparation of nanostructured electrolytes:
[0059] Sol-Gel Method: The precursors of conductive and electrolyte materials are dissolved in a solution to form a sol, which is then transformed into a nanostructured solid material through heat treatment.
[0060] Liquid phase deposition (CVD): This method uses chemical vapor deposition to deposit nanoparticles or thin films of conductive materials onto the surface of an electrolyte to form a conductive network.
[0061] Solution impregnation method: The electrolyte is immersed in a solution containing conductive nanomaterials, and then the conductive material is uniformly distributed inside the electrolyte by heat treatment or solvent evaporation to form a conductive network structure;
[0062] Mechanical mixing method: Conductive nanomaterials are mixed with electrolyte materials, and composite electrolyte materials are prepared through mechanical mixing or ball milling processes;
[0063] 3. Optimize ion diffusion pathways:
[0064] Forming a conductive network: By introducing conductive materials, an effective ion diffusion network is constructed to reduce the path resistance of ions in the electrolyte and improve the migration rate of ions. The conductive material is selected from carbon nanotubes and graphene.
[0065] Nanoscale structuring: Utilizing the high surface area and porosity of nanostructures, rapid diffusion of ions in electrolytes is promoted, improving the ionic conductivity of electrolytes. Nanostructures can provide more ion transport channels and reduce energy loss during ion migration.
[0066] 4. Cross-layer optimization:
[0067] Interface modification: By forming a tight interface between the electrolyte and the electrode, the ion transport path can be further optimized. An interface modification layer can be applied to the electrode-electrolyte contact surface to reduce the interface resistance and improve the overall conductivity. The interface modification layer adopts a conductive polymer coating.
[0068] Adjusting electrolyte thickness: Based on the distribution of the conductive network, the thickness of the electrolyte layer is adjusted to minimize the ion diffusion path and further optimize the efficiency of ion migration.
[0069] As an optimized technical solution, ionic conductivity is related to the ion concentration and mobility in the electrolyte, as expressed by the following equation:
[0070] σ=zFDρ
[0071] Where z is the charge number of the ion, F is the Faraday constant, D is the diffusion coefficient of the ion, and ρ is the concentration of the ion. By introducing conductive network materials, the diffusion coefficient D and the ion concentration ρ can be increased, thereby improving the conductivity of the electrolyte.
[0072] The surface effects of nanostructures significantly enhance the ion mobility of materials, typically manifesting as:
[0073]
[0074] Among them, D nanomaterial δ is the ion diffusion coefficient of nanostructured materials, D0 is the diffusion coefficient of ordinary materials, δ is the active region on the material surface, and r is the size of nanoparticles. The surface of nanostructures provides more active sites, which can enhance ion diffusion.
[0075] The conductivity of an electrolyte is usually temperature-dependent and can be expressed by the Arrhenius equation:
[0076]
[0077] Where σ(T) is the conductivity at temperature, σ0 is a constant, and E a The activation energy is E, where k is the Boltzmann constant. With the introduction of nanomaterials, due to their high surface area, the activation energy E of the electrolyte increases. a This can reduce the conductivity, thus allowing the electrolyte to maintain good conductivity at low temperatures.
[0078] The beneficial effects of this invention are:
[0079] By coating the capacitor surface with fluoride or ceramic coatings (such as titanium oxide), the contact between moisture and the internal electrolyte and electrodes is effectively isolated, significantly improving the capacitor's moisture resistance and reducing the corrosion of the electrolyte and electrode materials by moisture; the high-temperature resistance of the coating material can protect the capacitor and maintain stable performance in high-temperature environments. Even under high-temperature operating conditions, the coating can prevent electrolyte aging or decomposition, extending the capacitor's lifespan. Oxide coatings such as titanium oxide have excellent corrosion resistance, effectively preventing adverse reactions between the electrolyte and external corrosive gases or liquids, maintaining stable capacitor operation. By optimizing electrolyte materials (such as lithium-doped or conductive ceramic composite electrolytes), the conductivity decay of the electrolyte at low temperatures is reduced, allowing the capacitor to maintain high ionic conductivity even in low-temperature environments, ensuring normal capacitor operation. By improving the electrolyte's structural design, the negative impact of low temperatures on electrolyte performance is reduced, ensuring better performance stability of the capacitor at low temperatures. The use of multi-step lamination processes and vacuum sintering technology ensures that each layer of the capacitor is tightly bonded, avoiding bubbles or misalignment, improving overall density and mechanical strength, and enhancing capacitor reliability. Laser cutting technology precisely controls the capacitor's dimensions, ensuring alignment and stability between layers, further improving capacitor performance and lifespan. Attached Figure Description
[0080] Figure 1 This is a flowchart of the manufacturing steps of a stacked solid-state electrolytic capacitor provided by the present invention. Detailed Implementation
[0081] The present invention will now be further described in conjunction with the accompanying drawings and specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.
[0082] It should be noted that the terms "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship commonly used when the product of the invention is in use. They are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the invention.
[0083] In the description of this invention, it should also be noted that, unless otherwise explicitly specified and limited, the terms "set," "install," "connect," and "link" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.
[0084] Example 1:
[0085] This embodiment of a stacked solid-state electrolytic capacitor includes a capacitor body, which adopts a multi-layer stacked structure, each layer consisting of an electrode layer, a solid electrolyte layer and an isolation layer.
[0086] The electrode layer includes a positive electrode layer and a negative electrode layer, which are made of highly conductive metal and are responsible for conducting charges. It can be made of either aluminum or tantalum.
[0087] The fixed electrolyte layer uses a composite electrolyte to provide ion transport channels. The composite electrolyte can be either a polyethylene oxide (PEO) based composite solid electrolyte or a polyvinylidene fluoride (PVDF) based composite solid electrolyte.
[0088] The isolation layer prevents direct contact between the motor and the ion pathway;
[0089] The multi-layer stacked structure increases the effective electrode contact area per unit area and improves the capacitance.
[0090] Each layer of components in the stack is tightly bonded through high-pressure heat treatment to improve interface compatibility and mechanical strength.
[0091] In this embodiment, by coating the capacitor surface with a fluoride or ceramic coating (such as titanium oxide), the contact between moisture and the internal electrolyte and electrodes is effectively isolated, significantly improving the capacitor's moisture resistance and reducing the corrosion of the electrolyte and electrode materials by moisture. The high-temperature resistance of the coating material protects the capacitor and ensures stable performance under high-temperature environments. Even under high-temperature operating conditions, the coating prevents electrolyte aging or decomposition, extending the capacitor's service life. Oxide coatings such as titanium oxide have excellent corrosion resistance, effectively preventing adverse reactions between the electrolyte and external corrosive gases or liquids, thus maintaining stable capacitor operation.
[0092] Example 2:
[0093] In this embodiment, a method for manufacturing a stacked solid-state electrolytic capacitor is also provided, and the manufacturing steps are as follows:
[0094] A: Multi-step lamination:
[0095] (a1: Prepare materials for each layer: First, prepare the raw materials for the electrode layer, electrolyte layer and isolation layer, and ensure that the size, thickness and chemical properties of each material meet the requirements;
[0096] (a2: Pretreatment and cleaning: Before stacking, each layer of material is cleaned to remove surface impurities and oxides, ensuring good interlayer bonding;
[0097] (a3: Lamination stacking: Using a special laminator, the layers of material are stacked in sequence and appropriate pressure is applied. During multiple stacking processes, it is necessary to ensure that each layer of material is free from misalignment, air bubbles or defects.)
[0098] (a4: Heat treatment and cooling: The stacked components are heated to a certain temperature, which is set between 120°C and 200°C. Through heat treatment, the molecules between the materials are cross-linked to a certain extent, which enhances the interlayer bonding force.)
[0099] B: Vacuum sintering:
[0100] (b1: Stack heating: Sintering is carried out in a vacuum furnace at a temperature controlled between 300°C and 500°C. This temperature is sufficient to promote molecular movement in the material, but will not cause excessive thermal damage to the material.)
[0101] (b2: Create a vacuum environment: Remove residual gas and moisture from the material by vacuuming, further reduce the generation of bubbles and enhance the compactness of the material;
[0102] (b3: Cooling: After sintering, slowly cool to room temperature to avoid thermal stress caused by sudden temperature drop;
[0103] C: Laser cutting:
[0104] (c1: Size measurement: Measure the overall dimensions of the stack using precision instruments according to the design dimensions and requirements of the capacitors;)
[0105] (c2: Laser cutting: High-precision laser cutting equipment is used to cut the stack to ensure the flatness of the cut surface and the accuracy of the cut dimensions;
[0106] (c3: Post-processing: After cutting, edge processing or cleaning is required to remove small particles or heat-affected zones generated during the cutting process;
[0107] During sintering, atoms or molecules diffuse at high temperatures, forming a dense solid structure. The rate of diffusion can be expressed by the following formula:
[0108]
[0109] Where D is the diffusion coefficient, D0 is a constant, Q is the activation energy, R is the gas constant, and T is the temperature. As the sintering temperature increases, the diffusion coefficient increases, which promotes the bonding of the material.
[0110] The capacitance value is related to the area and spacing of the electrodes and the dielectric constant of the electrolyte. For stacked capacitors, the capacitance formula is:
[0111]
[0112] Where ε is the dielectric constant of the electrolyte, A is the effective area of the electrode, and d is the distance between the electrodes. In a stacked structure, the capacitance can be increased by increasing the effective area A and decreasing d.
[0113] The interfacial resistance of a capacitor is closely related to the contact quality between the electrolyte and the electrodes. Assume the interfacial resistance R... interface It is inversely proportional to the electrolyte conductivity σ and the contact area A between the electrodes:
[0114]
[0115] Increasing the uniformity and tightness of the electrode-electrolyte contact helps reduce interfacial resistance and improve capacitor performance.
[0116] Specifically, this also includes the fabrication of composite solid electrolytes, with the following steps:
[0117] Preparation of inorganic materials:
[0118] Highly conductive sulfide and oxide materials are used as matrix materials. Sulfides are characterized by their high ionic conductivity (up to 10 mS / cm) and mechanical flexibility, while oxides help stabilize interfacial chemistry and reduce interfacial resistance. Specifically, the sulfide materials used are the Li₂S-P₂S₅ system or Li₆PS₅X, where X = Br, Cl, I; and the oxide materials used are LiNbO₃ and Li₄Ti₅O₃. 12 One of them;
[0119] Polymer solution preparation:
[0120] Polyvinylidene fluoride (PVDF) is mixed with N-methylpyrrolidone solvent to form a homogeneous solution. These polymers play a role in bonding and flexibility modification in composite materials.
[0121] Mixing of composite materials:
[0122] Inorganic material powder and polymer solution are mixed in a ratio of 1:1.2. The mixture is then dispersed by ultrasonication or ball milling to ensure uniform material distribution. This step can improve the ion transport path and increase the overall ionic conductivity.
[0123] Membrane forming and heat treatment:
[0124] The mixture is coated or pressed into a film and then heat-treated at high temperature, controlled between 150°C and 200°C, to enhance the interfacial bonding between the sulfide and the polymer, thereby improving mechanical strength and ionic conductivity.
[0125] Adding dopants to composite solid electrolytes can optimize ion transport pathways and improve chemical stability. The steps are as follows:
[0126] Selecting the dopant: Choose either a lithium salt or a conductive ceramic based on the target performance. The lithium salt can be either LiCl or LiTFSI, and the conductive ceramic can be Li7La3Zr2O. 12 ;
[0127] Uniform dispersion: Lithium salt and ceramic particles are mixed in a specific ratio and uniformly dispersed in a polymer matrix (polyvinylidene fluoride). The ratio of lithium salt to ceramic particles is controlled between 1:1.5 and 1:2.
[0128] Heat treatment and curing: High-temperature heat treatment promotes interfacial fusion of materials, thereby reducing interfacial resistance;
[0129] This also includes coating an interface conditioning layer on the contact surface between the motor and the electrolyte, with the aim of reducing interfacial impedance and improving the bonding quality between the electrode and the electrolyte. The steps are as follows:
[0130] S1: Coating of the interface conditioning layer:
[0131] Conductive polymer coating: Polyaniline (PANI) and polypyrrole (PPy) conductive polymers are used to form a conductive bridge between the electrode and the electrolyte, reduce interfacial impedance, and enhance the migration of electrons and ions on the electrode surface;
[0132] Oxide coating: A thin layer of titanium oxide (TiO2) or aluminum oxide (Al2O3) is formed on the electrode surface. This oxide layer can prevent direct contact between the electrode and the electrolyte, reduce chemical reactions, and provide a stable interface.
[0133] S2: Plasma treatment:
[0134] By using plasma to create minute structural changes on the electrode surface, including porosimetry or surface activation, the binding force between the electrode surface and the electrolyte can be improved. Plasma treatment can clean the electrode surface and effectively activate the surface, thereby improving the reactivity at the interface.
[0135] The process involves plasma treatment of the electrode surface with a gas, which can be oxygen, nitrogen or argon, to form abundant oxygen functional groups, including -COOH and -OH, thereby enhancing the physical and chemical bonding between the electrode and the electrolyte.
[0136] S3: Chemical modification:
[0137] Different functional groups can be introduced on the electrode surface to improve the interfacial stability between the electrode and the electrolyte. These groups can form coordination or chemical bonds with ions in the electrolyte, enhance interfacial adhesion, and thus reduce resistance. Functional groups include amino and carboxyl groups.
[0138] To improve the environmental resistance of capacitors, including moisture resistance, high temperature resistance, and corrosion resistance, and to optimize the internal structural design to reduce the decay of electrolyte conductivity at low temperatures, a protective coating is added.
[0139] The steps are as follows:
[0140] Coating selection: Select coating materials suitable for high temperature and humid environments, including fluoride coatings or ceramic coatings, which have excellent corrosion resistance, high temperature resistance and moisture resistance. Fluoride coatings can be made of fluorinated polytetrafluoroethylene, and ceramic coatings can be made of alumina or titanium dioxide.
[0141] Surface treatment: The capacitor surface is treated, including plasma cleaning and chemical pretreatment, to improve the adhesion and uniformity of the coating;
[0142] Coating application: Applying a coating by spraying, dipping, brushing, or chemical vapor deposition;
[0143] Curing: Heat treatment is used to cure the coating, improving its durability and adhesion;
[0144] This also includes introducing conductive networks or nanostructured pathways into the electrolyte to optimize ion diffusion. The steps are as follows: 1: Select conductive network or nanostructured materials:
[0145] Conductive polymers: Polyaniline (PANI), polypyrrole (PPy), or polyethylene terephthalate (PET) conductive polymers are selected, which have good conductivity and high flexibility, and are suitable for optimizing the ion conduction of electrolytes;
[0146] Conductive ceramics: Alumina (Al2O3), zinc oxide (ZnO) or Li6PS5X are selected to effectively improve the ionic conductivity of the electrolyte, especially in high and low temperature environments;
[0147] Carbon nanomaterials: Carbon nanotubes (CNTs) or graphene are selected because their excellent conductivity and high surface area can significantly improve the conductivity of electrolytes and optimize ion migration pathways.
[0148] 2: Preparation of nanostructured electrolytes:
[0149] Sol-Gel Method: The precursors of conductive and electrolyte materials are dissolved in a solution to form a sol, which is then transformed into a nanostructured solid material through heat treatment.
[0150] Liquid phase deposition (CVD): This method uses chemical vapor deposition to deposit nanoparticles or thin films of conductive materials onto the surface of an electrolyte to form a conductive network.
[0151] Solution impregnation method: The electrolyte is immersed in a solution containing conductive nanomaterials, and then the conductive material is uniformly distributed inside the electrolyte by heat treatment or solvent evaporation to form a conductive network structure;
[0152] Mechanical mixing method: Conductive nanomaterials are mixed with electrolyte materials, and composite electrolyte materials are prepared through mechanical mixing or ball milling processes;
[0153] 3. Optimize ion diffusion pathways:
[0154] Forming a conductive network: By introducing conductive materials, an effective ion diffusion network is constructed to reduce the path resistance of ions in the electrolyte and improve the migration rate of ions. The conductive material is selected from carbon nanotubes and graphene.
[0155] Nanoscale structuring: Utilizing the high surface area and porosity of nanostructures, rapid diffusion of ions in electrolytes is promoted, improving the ionic conductivity of electrolytes. Nanostructures can provide more ion transport channels and reduce energy loss during ion migration.
[0156] 4. Cross-layer optimization:
[0157] Interface modification: By forming a tight interface between the electrolyte and the electrode, the ion transport path can be further optimized. An interface modification layer can be applied to the electrode-electrolyte contact surface to reduce the interface resistance and improve the overall conductivity. The interface modification layer adopts a conductive polymer coating.
[0158] Adjusting electrolyte thickness: Based on the distribution of the conductive network, the thickness of the electrolyte layer is adjusted to minimize the ion diffusion path and further optimize the efficiency of ion migration.
[0159] By introducing conductive networks or nanostructured pathways into the electrolyte, the diffusion path of ions in the electrolyte is optimized, reducing the internal resistance during ion migration. These conductive networks or nanostructures significantly improve the ionic conductivity of the electrolyte by providing more conductive channels, increasing the surface area, and reducing the resistance of the ion diffusion path.
[0160] Enhanced ionic conductivity: Conductive nanostructures can reduce barriers to ion migration and increase the free migration speed of ions. Conductive materials provide a continuous conductive path, which greatly improves the conductivity of electrolytes.
[0161] Reduce the internal resistance of the electrolyte: Nanostructured electrolyte materials can provide more conductive paths, reduce resistance in electron and ion migration, thereby improving the overall capacitance and charge / discharge efficiency of the capacitor.
[0162] Ionic conductivity is related to the ion concentration and mobility in the electrolyte, and can be expressed by the following equation:
[0163] σ=zFD ρ
[0164] Where z is the charge number of the ion, F is the Faraday constant, D is the diffusion coefficient of the ion, and ρ is the concentration of the ion. By introducing conductive network materials, the diffusion coefficient D and the ion concentration ρ can be increased, thereby improving the conductivity of the electrolyte.
[0165] The surface effects of nanostructures significantly enhance the ion mobility of materials, typically manifesting as:
[0166]
[0167] Among them, D nanomaterialδ is the ion diffusion coefficient of nanostructured materials, D0 is the diffusion coefficient of ordinary materials, δ is the active region on the material surface, and r is the size of nanoparticles. The surface of nanostructures provides more active sites, which can enhance ion diffusion.
[0168] The conductivity of an electrolyte is usually temperature-dependent and can be expressed by the Arrhenius equation:
[0169]
[0170] Where σ(T) is the conductivity at temperature, σ0 is a constant, and E a The activation energy is E, where k is the Boltzmann constant. With the introduction of nanomaterials, due to their high surface area, the activation energy E of the electrolyte increases. a This can reduce the conductivity, thus allowing the electrolyte to maintain good conductivity at low temperatures.
[0171] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Various combinations, modifications, or equivalent substitutions of the technical solutions of the present invention by those skilled in the art do not depart from the spirit and scope of the technical solutions of the present invention and should be covered within the scope of the claims of the present invention.
Claims
1. A stacked solid electrolytic capacitor, characterized in that: The capacitor body comprises a multi-layer stacking structure, each layer of which is composed of an electrode layer, a solid electrolyte layer and an isolation layer; The electrode layer includes a positive electrode layer and a negative electrode layer, which are made of a highly conductive metal and are responsible for conducting charges, and can be made of one of aluminum and tantalum; The fixed electrolyte layer uses a composite electrolyte to provide an ion transmission channel. The composite electrolyte can be a polyethylene oxide (PEO)-based composite solid electrolyte or a polyvinylidene fluoride (PVDF)-based composite solid electrolyte. The isolation layer prevents direct contact between the motor and the ion path; Adopting a multi-layer stacking structure to increase the effective electrode contact area per unit area and improve the capacitance; Each layer of components in the stack is tightly bonded through high-pressure heat treatment to improve interface compatibility and mechanical strength.
2. A method for manufacturing a stacked solid electrolytic capacitor, characterized in that: The production steps are as follows: A: Multi-step lamination: (a1: Prepare the materials for each layer: First, prepare the raw materials for the electrode layer, electrolyte layer and isolation layer, and ensure that the size, thickness and chemical properties of each layer meet the requirements; (a2: Pretreatment and cleaning: Before stacking, each layer of material is cleaned to remove surface impurities and oxides to ensure good interlayer bonding; (a3: Lamination stacking: Use a special laminator to stack the layers of materials in order and apply appropriate pressure. During multiple stacking processes, it is necessary to ensure that each layer of material has no misalignment, bubbles or defects; (a4: Heat treatment and cooling: The stacked components are heated to a certain temperature, which is set between 120℃ and 200℃. The molecules between the materials are cross-linked to a certain extent through heat treatment to enhance the bonding force between the layers; B: Vacuum sintering: (b1: Stack heating: sintering is carried out in a vacuum furnace, and the temperature is controlled between 300℃ and 500℃, which is high enough to promote molecular movement in the material but will not cause excessive thermal damage to the material; (b2: Create a vacuum environment: Remove the residual gas and moisture in the material by vacuuming, further reduce the generation of bubbles and enhance the density of the material; (b3: Cooling: After sintering, slowly cool to room temperature to avoid thermal stress caused by sudden temperature drop; C: Laser cutting: (c1: Dimension measurement: According to the design size and requirements of the capacitor, use precision instruments to measure the overall size of the stack; (c2: Laser cutting: Use high-precision laser cutting equipment to cut the stack to ensure the flatness of the cutting surface and the accuracy of the cutting size; (c3: Post-processing: After cutting, edge processing or cleaning is required to remove tiny particles or heat-affected areas generated during the cutting process.
3. The method for manufacturing a stacked solid electrolytic capacitor according to claim 2, characterized in that: It also includes the preparation of a composite solid electrolyte, the steps are as follows: Preparation of inorganic materials: Highly conductive sulfide materials and oxide materials are used as matrix materials. Sulfide is characterized by its high ionic conductivity (up to 10mS / cm) and mechanical flexibility, while oxide helps to stabilize the interface chemistry and reduce the interface resistance. Among them, the sulfide material uses Li2S-P2S5 system or Li6PS5X, X=Br,Cl,I, and the oxide material uses LiNbO3, Li4Ti5O 12 One of; Polymer solution preparation: Mixing polyvinylidene fluoride (PVDF) with N-methylpyrrolidone solvent to form a homogeneous solution, these polymers play a role in bonding and improving flexibility in the composite material; Mixing of composite materials: Mixing inorganic material powder and polymer solution in proportion, the ratio of inorganic material powder to polymer solution is 1:1.2, and using ultrasonic dispersion or ball milling to ensure uniform distribution of materials. This step can improve the ion transmission path and increase the overall ion conductivity; Film forming and heat treatment: The mixture is coated or pressed into a film and heat treated at high temperature, controlled at 150°C to 200°C, to enhance the interfacial bonding between the sulfide and the polymer, thereby improving the mechanical strength and ionic conductivity.
4. The method for manufacturing a stacked solid electrolytic capacitor according to claim 2, characterized in that: Adding dopants to composite solid electrolytes can optimize ion transport pathways and improve chemical stability. The steps are as follows: Select dopant: Select one of lithium salt and conductive ceramic according to the target performance. The lithium salt is LiCl or LiTFSI, and the conductive ceramic is Li7La3Zr2O 12 ; Uniform dispersion: lithium salt and ceramic particles are mixed in a specific ratio and evenly dispersed in a polymer matrix (polyvinylidene fluoride, with the ratio of lithium salt to ceramic particles controlled between 1:1.5 and 1:2; Heat treatment and curing: High temperature heat treatment promotes the interface fusion of materials, thereby reducing the interface resistance.
5. The method for manufacturing a stacked solid electrolytic capacitor according to claim 2, characterized in that: It also includes coating an interface adjustment layer on the contact surface between the motor and the electrolyte, the purpose of which is to reduce the interface impedance and improve the bonding quality between the electrode and the electrolyte, the steps are as follows: S1: Coating of interface adjustment layer: Conductive polymer coating: using polyaniline (PANI) and polypyrrole (PPy) conductive polymers to form a conductive bridge between the electrode and the electrolyte, reduce the interface impedance, and enhance the migration of electrons and ions on the electrode surface; Oxide coating: A thin titanium oxide (TiO2) or aluminum oxide (Al2O3) layer is formed on the electrode surface. This oxide layer prevents direct contact between the electrode and the electrolyte, reduces chemical reactions, and provides a stable interface. S2: Plasma treatment: Plasma treatment can clean the electrode surface and effectively activate the surface to improve the reactivity at the interface by using plasma to create tiny structural changes on the electrode surface, including porosity or surface activation, to improve the bonding between the electrode surface and the electrolyte; The treatment process includes plasma treatment of the electrode surface in a gas, which can be one of oxygen, nitrogen or argon, so that the surface forms abundant oxygen functional groups, including -COOH and -OH, thereby enhancing the physical and chemical bonding between the electrode and the electrolyte; S3: Chemical modification: The interface stability between the electrode and the electrolyte is improved by introducing different functional groups on the electrode surface. These groups can form coordination or chemical bonds with the ions in the electrolyte, enhance the interfacial adhesion, and thus reduce the resistance. The functional groups include amino and carboxyl groups.
6. The method for manufacturing a stacked solid electrolytic capacitor according to claim 2, characterized in that: In order to improve the environmental resistance of capacitors, including moisture resistance, high temperature resistance and corrosion resistance, as well as optimize the internal structure design to reduce the attenuation of electrolyte conductivity in low temperature environments, add protective coatings, The steps are as follows: Coating selection: Choose coating materials suitable for high temperature and humid environments, including fluoride coatings or ceramic coatings, which have excellent corrosion resistance, high temperature resistance and moisture resistance. Fluoride coatings can be made of fluorinated polytetrafluoroethylene, and ceramic coatings can be made of one of aluminum oxide or titanium oxide; Surface treatment: Treatment is performed on the capacitor surface, including plasma cleaning and chemical pretreatment, to improve the adhesion and uniformity of the coating; Coating Application: Coatings are applied by spraying, dipping, brushing or chemical vapor deposition; Curing: Use heat treatment to cure the coating, improving its durability and adhesion.
7. The method for manufacturing a stacked solid electrolytic capacitor according to claim 2, characterized in that: It also includes introducing a conductive network or nanostructured path in the electrolyte to optimize ion diffusion. The steps are as follows: 1: Select a conductive network or nanostructured material: Conductive polymer: Polyaniline (PANI), polypyrrole (PPy) or polyethylene terephthalate (PET) conductive polymers are selected, which have good conductivity and high flexibility and are suitable for optimizing the ion conduction of electrolytes; Conductive ceramics: Alumina (Al2O3), zinc oxide (ZnO) or Li6PS5X are used to effectively improve the ionic conductivity of the electrolyte, especially in high and low temperature environments; Carbon nanomaterials: Carbon nanotubes (CNTs) or graphene are used because of their excellent conductivity and high surface area, which can significantly improve the conductivity of the electrolyte and optimize the ion migration path; 2: Preparation of nanostructured electrolytes: Sol-Gel Method: The precursors of the conductive material and the electrolyte material are dissolved in a solution to form a sol, which is then converted into a nanostructured solid material by heat treatment; Liquid phase deposition method (CVD): Through chemical vapor deposition method, nanoparticles or thin films of conductive materials are deposited on the surface of the electrolyte to form a conductive network; Solution impregnation method: The electrolyte is immersed in a solution containing conductive nanomaterials, and then the conductive materials are evenly distributed inside the electrolyte through heat treatment or solvent evaporation to form a conductive network structure; Mechanical mixing method: Mix the conductive nanomaterials with the electrolyte materials to prepare composite electrolyte materials through mechanical mixing or ball milling process; 3: Optimize ion diffusion path: Forming a conductive network: By introducing conductive materials, an effective ion diffusion network is constructed to reduce the path resistance of ions in the electrolyte and increase the migration rate of ions. The conductive material is selected from carbon nanotubes and graphene; Nano-scale structuring: The high surface area and porosity of the nanostructure are used to promote the rapid diffusion of ions in the electrolyte and improve the ionic conductivity of the electrolyte. The nanostructure can provide more ion transmission channels and reduce the energy loss during ion migration. 4: Cross-layer optimization: Interface modification: By forming a tight interface between the electrolyte and the electrode, the ion transmission path is further optimized. An interface modification layer can be applied to the contact surface between the electrode and the electrolyte to reduce the interface resistance and improve the overall conductivity. The interface modification layer uses a conductive polymer coating; Adjusting electrolyte thickness: According to the distribution of the conductive network, the thickness of the electrolyte layer is adjusted to shorten the ion diffusion path and further optimize the efficiency of ion migration.
8. The method for manufacturing a stacked solid electrolytic capacitor according to claim 7, characterized in that: Ionic conductivity is related to the ion concentration and mobility in the electrolyte and is expressed by the following equation: σ=zFDρ Among them, z is the charge number of the ion, F is the Faraday constant, D is the diffusion coefficient of the ion, and ρ is the concentration of the ion. By introducing conductive network materials, the diffusion coefficient D and the ion concentration ρ can be increased, thereby improving the conductivity of the electrolyte; The surface effect of nanostructures greatly improves the ion mobility of materials, which is usually manifested as: Among them, D nanomaterial is the ion diffusion coefficient of the nanostructured material, D0 is the diffusion coefficient of the ordinary material, δ is the active area on the material surface, r is the size of the nanoparticle, and the surface of the nanostructure provides more active sites, which can enhance ion diffusion; The conductivity of an electrolyte is usually temperature dependent and can be expressed by the Arrhenius equation: Where σ(T) is the conductivity at temperature, σ0 is a constant, and E a is the activation energy, k is the Boltzmann constant. After the introduction of nanomaterials, due to the high surface area of nanomaterials, the activation energy E of the electrolyte a It can be reduced so that the electrolyte can still maintain good conductivity at low temperatures.